Epidemiology, treatment and outcome of patients with lower respiratory tract infection presenting to emergency departments with dyspnoea (AANZDEM and EuroDEM studies). (3rd August 2020) - Rousseau, Geoffroy; Keijzers, Gerben; van Meer, Oene; Craig, Simon; Karamercan, Mehmet; Klim, Sharon; Body, Richard; Kuan, Win Sen; Harjola, Veli‐Pekka; Jones, Peter; Verschuren, Franck; Holdgate, Anna; et al.
Abstract: Objective: Lower respiratory tract infection (LRTI) is a frequent cause of dyspnoea in EDs, and is associated with considerable morbidity and mortality. We described and compared the management of this disease in Europe and Oceania/South‐East Asia (SEA) cohorts. Methods: We conducted a prospective cohort study with three time points in Europe and Oceania/SEA. We included in this manuscript patients presenting to EDs with dyspnoea and a diagnosis of LRTI in ED. We collected comorbidities, chronic medication, clinical signs at arrival, laboratory parameters, ED management and patient outcomes. Results: A total of 1389 patients were included, 773 in Europe and 616 in SEA. The European cohort had more comorbidities including chronic heart failure, obesity, chronic obstructive pulmonary disease and smoking. Levels of inflammatory markers were higher in Europe. There were more patients with inflammatory markers in Europe and more hypercapnia in Oceania/SEA. The use of antibiotics was higher in SEA (72.2% vs 61.8%, P < 0.001) whereas intravenous diuretics, non‐invasive and invasive ventilation were higher in Europe. Intensive care unit admission rate was 9.9% in Europe cohort and 3.4% in Oceania/SEA cohort. ED mortality was 1% and overall in‐hospital mortality was 8.7% with no differences between regions. Conclusions: More patients with LRTI in Europe presented with cardio‐respiratory comorbidities, they received more adjunct therapies and had a higher intensive care unit admission rate than patients from Oceania/SEA, although mortality was similar between the two cohorts.